Rendering medical aid to acne patients. Results of an expert examination of the quality of medical aid - I. O. Smirnova; M. A. Karachevtseva; S. M. Mikhailov; Ye. A. Kulikova; I. S. Kolova; T. S. Smirnova; V. Yu. Dudko; Ya. G. Petunova; N. V. Shin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To obtain information on typical errors in medical aid rendered to acne patients in dermatovenerology dispensaries in St. Petersburg in order to develop measures to improve the quality of medical aid rendered to this group of patients. Materials and methods. The authors conducted a special expert examination of 55 patients with acne who received treatment at St. Petersburg dermatovenerology dispensaries in 2013. The quality of medical aid was assessed using the Automated Expert Examination Technique (hereinafter referred to as AEET). Major results. The percentage of cases when medical aid of due quality was rendered to acne patients was 49%. Treatment and diagnostics errors prevailed in the structure of errors in medical aid. Errors in treatment were mainly a wrong combination of drugs, simultaneous administration of external and systemic antibacterial drugs, delayed comedolytic therapy and pathogenically infeasible therapy. Errors in diagnostics included absence of indications of the form and/or severity of acne. The most important error in the collection of information was absence of gynecology examinations for women to determine whether peroral contraceptives were necessary including in case of the administration of isotretinoin. Conclusion. The similarity of errors in medical aid rendered for acne as well as high percentage of errors relating to medical aid rendered to patients demand the development of consistent measures to improve the quality of medical aid rendered to such patients and repeated expert examination using preliminary (prompt) control of the quality of medical aid.